Progress and Barriers Towards Elimination of Chronic Hepatitis C in Children - Pluta, Magdalena; Pokorska-Śpiewak, Maria; Aniszewska, Małgorzata; Kowalik-Mikołajewska, Barbara; Marczyńska, Magdalena (Klinische Pädiatrie, 2020)
Chronic hepatitis C (CHC) is a global health burden. Mother-to-child transmission (MTCT) accounts for most HCV infections in pediatric patients. Spontaneous viral clearance may occur in early childhood but is uncommon thereafter. Infection is usually asymptomatic during childhood, although without an effective treatment, vertically infected children may develop serious liver complications including cirrhosis and hepatocellular carcinoma in adulthood. Despite the lack of vaccine against hepatitis C and effective post-exposure methods of prevention of MTCT, treatment with direct-acting antiviral agents (DAAs) raised the prospect of eliminating HCV on a population level. Highly effective, well-tolerated, oral, and interferon-free regimens of short duration have revolutionized treatment of CHC. However, access to these therapies might be limited because of its high cost. In this review, we provide the current state of knowledge on the epidemiology, testing, monitoring and treating of HCV in children. We outline the remaining gaps in therapy and barriers to disease eradication.
Keywords: hepatitis C; HCV in children; direct-acting antivirals; DAA; Mother-to-child transmission